Estudio de la situación socio-lingüística del kichwa en la comunidad de Quinchuquí. - Santillán Amaguaña, Luis Alberto (2015)
This study was carried out thanks to the collaboration of the inhabitants of the community of Quinchuqui, people that I've visited I gladly attended and helped me with clear and accurate information to a successful culmination with this work. Of the collected information, demonstrate much more clearly those who use and those who do not use this language kichwa, their causes and their consequences. Through surveys, children, youth, teens, adults, as well as community leaders and teachers of the schools in the sector, were able to collect accurate information on the situation. Also was able to participate in the social activities organized by the community, as: minga, the celebration of the Inti Raymi, religious activities such as the mass or worship, these social activities, it became clear that adults and older adults use the kichwa as language of communication at all times, as the young people, adolescents and childrenused over the Spanish. To have a result separately had to be classified by age, this was done with the purpose of verifying those who use and those who do not use this language, and what are the possible causes by which this language is minimized. However, you can see that a part of the young population is determined to fight for the recovery and revitalization of this language. Young students, both secondary education and higher education are aware of the loss of cultural values, so feel the need to restore, develop, and retain their mother tongue.